2018
DOI: 10.7150/jca.22280
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Features and Survival Outcomes of Different Histological Subtypes in Triple-negative Breast Cancer

Abstract: Purpose: To determine the clinicopathological features and survival outcomes of triple-negative breast cancer (TNBC) according to different histological subtypes.Methods: Using the Surveillance, Epidemiology, and End Results database, we included TNBC cases in 2010-2013. The effect of histological subtype on breast cancer-specific survival (BCSS) and overall survival (OS) were analyzed using univariate and multivariate analyses.Results: A total of 19,900 patients were identified. Infiltrating ductal carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 35 publications
5
43
1
Order By: Relevance
“…In another aspect, the pathomorphological indicators, as the results of genetic changes of tumor cells, should also be well studied. Previous study had reported that specific histologic subtypes showed significant differences in the percentage of distant metastasis, and invasive lobular carcinoma was considered as a subtype with highest metastasis probability . However, another study reported that breast cancer subtypes based on hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2) status had specific preferential site of distant organ metastases .…”
Section: Introductionmentioning
confidence: 99%
“…In another aspect, the pathomorphological indicators, as the results of genetic changes of tumor cells, should also be well studied. Previous study had reported that specific histologic subtypes showed significant differences in the percentage of distant metastasis, and invasive lobular carcinoma was considered as a subtype with highest metastasis probability . However, another study reported that breast cancer subtypes based on hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2) status had specific preferential site of distant organ metastases .…”
Section: Introductionmentioning
confidence: 99%
“…Based on its biomarker [oestrogen receptor/progesterone receptor/human epidermal growth factor receptor 2 (ER/PR/HER2)] profile and molecular profiling, it is classified as a triple‐negative and basal‐like carcinoma . However, in contrast to other basal‐like triple‐negative mammary carcinomas and salivary gland ACCs, breast ACC in general has a favourable prognosis . A variant of breast ACC, referred to as the solid variant of ACC with basaloid features, has been reported to have a more aggressive biological behaviour …”
Section: Introductionmentioning
confidence: 99%
“…3 However, in contrast to other basal-like triple-negative mammary carcinomas and salivary gland ACCs, breast ACC in general has a favourable prognosis. [4][5][6] A variant of breast ACC, referred to as the solid variant of ACC with basaloid features, has been reported to have a more aggressive biological behaviour. [7][8][9] Studies have demonstrated that the MYB-NFIB fusion, resulting from translocation t(6;9)(q22-23; p23-24) involving the oncogene MYB on chromosome 6q and the gene for transcription factor NFIB on chromosome 9p, is specific to ACCs from various sites, including breast.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, combination approaches including chemotherapy, surgery, radiotherapy, targeted therapy and hormonal therapy have proven more successful than conventional single treatment methods . However, patients with TNBC, characterized by lack of expression of human epithelial growth factor receptor‐2, estrogen, progesterone receptor (ER − , PR − , Her2/neu − ) have poor prognosis . This is because therapy for TNBC patients remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, patients with TNBC, characterized by lack of expression of human epithelial growth factor receptor-2, estrogen, progesterone receptor (ER À , PR À , Her2/neu À ) have poor prognosis. 4,5 This is because therapy for TNBC patients remains limited.…”
Section: Introductionmentioning
confidence: 99%